Beasts of Speech: Constructing Marginal Narrative in the 15th-Century Edition of “Stefanit and Ichnilat” - M. V. Kaplun (Научный диалог, 2025)
This article explores the principles of constructing marginal narratives within the translated Old Russian text “Stefanit and Ichnilat,” specifically its 15th-century edition. The novelty of this study lies in its pioneering inquiry into the potential for identifying marginal narrative practices in Old Russian texts from this period. It is revealed that the marginality of the narrative, as perceived by the Old Russian reader, is facilitated by the distinctive narrative structure of the text. The authors’ use of the Slavic version of the original work results in the creation of a plot that is engaging through a series of interwoven stories. The study demonstrates that in this Old Russian work with Eastern themes, the use of dialogue as a primary narrative device begins to function as a necessary foundation for constructing a separate narrative layer. It is emphasized that this effect is achieved through a story-within-a-story format narrated by non-anthropomorphic narrators who are simultaneously characters and storytellers. The analysis reveals that the “unnaturalness” of the narrative is uncovered through the additional subtext of the work. The author concludes that the pronounced equality between beast-heroes and the narrator, the duality of images, the effect of dual worlds, and the inventive work of the scribe with the text allow for viewing this monument within the context of the poetics of reflective traditionalism.